FOLK MEDICINE AMONG TRIBE PEOPLE- A REVIEW - Sood, *Tanvi; Pathak, Mohit; Gupta, Chandni (International Journal of Ayurveda and Pharma Research, 2019)
Today ancient Ayurvedic texts have been researched and a lot of hidden knowledge has been brought to surface light and Ayurveda is becoming one of the leading scientific way of preserving and promoting a healthy life. On the other-hand we do not know much about another type of medicine which is more ancient, equally efficacious and widely practised by its adherents: Folk medicines. Folk medicine was practised during Atharva-Vedic period and it is still practised in 21st century by tribal people, villagers and even by some people of cities who still adheres to their ancestor knowledge in India. Folk medicine has its own concept of causation of disease, diagnostic techniques and treatment. In history of Indian medicine little or almost no attention has been given to folk medicine, on the other-hand tribal and village people believe in folk medicine as it fits in with their culture and way of thinking. If we want that these people can derive benefit from Ayurveda or Modern medicine then we have to take pain to see that today’s medicine is presented to them in such a way that it is ‘acceptable’ to them. We can make it ‘acceptable’ only if we know what they believe in. So here effort was made to recollect knowledge about folk medicine in india so that it not remain patchy and inadequate and helps to promote healthy life.